2023
DOI: 10.1001/jamanetworkopen.2023.9612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Low-level Red Light on Myopia Prevention Among Children in China With Premyopia

Abstract: ImportanceMyopia is a global concern, but effective prevention measures remain limited. Premyopia is a refractive state in which children are at higher risk of myopia, meriting preventive interventions.ObjectiveTo assess the efficacy and safety of a repeated low-level red-light (RLRL) intervention in preventing incident myopia among children with premyopia.Design, Setting, and ParticipantsThis was a 12-month, parallel-group, school-based randomized clinical trial conducted in 10 primary schools in Shanghai, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Two recent studies explored the possibility of using atropine for myopia prevention and reported opposite findings. For 650-nm LLRL, a clinical trial reported a 54.1% reduction in incident myopia among children with premyopia within 12 months . In our study, the 1-year myopia incidences were 7.1% and 23.2% for the LLRL and control groups, respectively, which was a 69.4% reduction.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Two recent studies explored the possibility of using atropine for myopia prevention and reported opposite findings. For 650-nm LLRL, a clinical trial reported a 54.1% reduction in incident myopia among children with premyopia within 12 months . In our study, the 1-year myopia incidences were 7.1% and 23.2% for the LLRL and control groups, respectively, which was a 69.4% reduction.…”
Section: Discussionsupporting
confidence: 56%
“…For 650-nm LLRL, a clinical trial reported a 54.1% reduction in incident myopia among children with premyopia within 12 months. 49 In our study, the 1-year myopia incidences were 7.1% and 23.2% for the LLRL and control groups, respectively, which was a 69.4% reduction. For children without myopia but at high risk of myopia (eg, when the SER progresses more than −0.75 D per year), the 650-nm LLRL can be a potential treatment option; however, further ethical exploration is needed in this regard.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In animal studies, the duration of red light exposure was generally for the entire waking period (12-14 h per day), while protocols in children use 3 min of red light exposure twice a day. Since 2021, over 24 papers have been published on red light therapy for myopia, [2][3][4][5][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] including three review papers. [27][28][29] Eyerising International, manufacturer of the Eyerising Myopia Management Device, advertises the instrument for use in children as young as 3 years old, with online claims that over 100,000 children have been or are currently being treated.…”
Section: Red Light Instruments For Myopia Exceed Safety Limits Lisa A...mentioning
confidence: 99%
“…20 Although the mechanism of action is not fully understood, this device emits a red light (650 nm) that seems to improve scleral hypoxia and thus prevent myopia progression. 20,60 RCTs evaluating myopia control with this treatment are limited. Chen et al 34 and Xiong et al 33 reported the highest rebound effect after LLLT cessation compared with the other myopia control treatments included in this systematic review.…”
Section: Low-level Light Therapymentioning
confidence: 99%